STUDY OF WAVE ENERGY POTENTIAL IN NORTHERN SEA OF PAPUA - Rushdi, Muhammad
Behind the ecological crisis, the high demand for energy, and its fulfillment by fossil sources, ocean wave becomes an alternative renewable resource with high power density. This study was carried out by Simulating Wave Nearshore (SWAN) model in period of December 1, 2014 –November 30, 2018. Wind data was taken from ECMWF Era Interim while bathymetry data obtained from GEBCO with resolution of 30 seconds. The result shows that significant wave height and wave energy is higher at offshore (1-1.2 m and 1,5-1,7 MWh/m) than nearshore (0.7-0.9 m and 1-1,3 MWh/m). The most energetic season and month are in DJF period and February. While the weakest occurred in the JJA period and July. Wind direction shifting due to monsoon seasons does not really affect wave direction because the waves are dominated by swell. Based on three points studied, Northern Supiori has the highest wave energy potential among Amberbaken and Demta with average significant wave heights 0,96 m and energy transport of 3.27 kW / m.